Association of Insomnia, Depressive Disorders, and Mood Disorders as Risk Factors With Breast Cancer: A Nationwide Population-Based Cohort Study of 232,108 Women in Taiwan - Liu, Hui-Pu; Wei, James Cheng-Chung; Yip, Hei-Tung; Yeh, Ming-Hsin (Frontiers in Oncology, 2021)
Background Insomnia, depressive disorders, and to a more general view, mood disorders are raising people’s concerns and causing disability of life. Herein, we try to seek the association of such illnesses with subsequent breast cancer. Methods This population-based, retrospective cohort study used data from the Taiwan National Health Insurance Research Database. This study included 232,108 women diagnosed with insomnia, depressive disorders, and mood disorders from January 1, 2000 to December 31, 2013. Physician diagnosed insomnia, depressive disorders, or mood disorders using outpatient and inpatient records before diagnosis of breast cancer. Cox proportional hazards regression analysis is adjusted for women with insomnia, depressive disorders, mood disorders, and other factors like insured amount, urbanization, and comorbidities such as having subsequent breast cancer. Results Sleep medication was associated with a significantly increased incidence rate of breast cancer (aHR = 1.23 (95% CI = 1.13, 1.35), p < 0.001). Insomnia was associated with significant increased hazard of breast cancer (aHR = 1.16 (95% CI = 1.07, 1.27), p < 0.001). Annual insured amount >20,000 (TWD), high urbanization area, and hyperlipidemia were associated with increased hazard of breast cancer (aHR = 1.13 (95% CI = 1.01, 1.27), p = 0.04; aHR = 1.41 (95% CI = 1.17, 1.71), p < 0.001; aHR = 1.14 995% CI = 1.02, 1.29), p = 0.02, respectively). There was a positive correlation between depressive disorders and increased incidence rate of breast cancer but not statistically significant (aHR = 1.11 (95% CI = 0.99, 1.25), p = 0.08). Mood disorders were not associated with increased hazard (aHR = 1.11 (95% CI = 0.91, 1.34), p = 0.31). Conclusion In this study, women with insomnia had increased risk of breast cancer, particularly those in high urbanization or with high insured amounts. Sleep medication (benzodiazepine (BZD) or non-BZD) and hyperlipidemia were independently associated with a higher hazard ratio of breast cancer. Insomnia along with sleep medication did not yield more hazards than each alone. Mood disorders appeared to be not associated with subsequent breast cancer. However, depressive disorders, the subgroups of mood disorders, could possibly increase the incidence rate of breast cancer though not statistically significant.